Neurology : a Queen Square textbook - Clarke, Charles (Charles R. A.); National Hospital for Neurology and Neurosurgery (London, England); Institute of Neurology, Queen Square; Wiley InterScience (Online service) (Chichester, UK ; Hoboken, NJ : Wiley-Blackwell, 2009)
Neurology: A Queen Square Textbook is a remarkable fusion of modern neuroscience with traditional neurology that will inform and intrigue trainee and experienced neurologists alike . Modern neuroscience has penetrated exciting and divers.
Neurology worldwide : the burden of neurological disease / Simon Shorvon -- Nervous system structure and function / Charles Clarke, Roger Lemon -- The language of neurology : symptoms, signs and basic investigations / Charles Clarke [and others] -- Stroke and cerebrovascular diseases / Nicholas Losseff, Martin Brown, Joan Grieve -- Movement disorders / Niall Quinn [and others] -- Epilepsy and related disorders / Simon Shorvon [and others] -- Cognitive impairment and dementia / Martin Rossor [and others] -- Infection in the nervous system / Robin Howard, Hadi Manji -- Nerve and muscle disease / Michael Lunn [and others] -- Multiple sclerosis and demyelinating diseases / Siobhan Leary [and others] -- Headache / Peter Goadsby -- Cranial nerve disorders / Paul Jarman [and others] -- Neuro-ophthalmology / Gordon Plant [and others] -- Neuro-otology : problems of dizziness, balance and hearing / Rosalyn Davies [and others] -- Spinal cord disorders / Simon Farmer [and others] -- Cerebellar ataxias and related conditions / Nicholas Wood -- Restorative and rehabilitation neurology / Richard Greenwood [and others] -- Toxic, metabolic and physical insults to the nervous system and inborn errors of metabolism / Robin Howard [and others] -- Disorders of consciousness, intensive care neurology and sleep / Robin Howard [and others] -- Neuro-oncology / Jeremy Rees [and others] -- Psychiatry and neurology / Michael Trimble -- Pain / Geoffrey Schott -- Autonomic dysfunction / Christopher Mathias -- Uro-neurology / Clare Fowler, Sohier Elneil -- Systemic conditions and neurology / David Werring [and others].
Includes bibliographical references and index.
Print version record.
Keywords: Nervous system -- Diseases -- Textbooks; Neurology -- Textbooks; Nervous System Diseases; Neurology; HEALTH & FITNESS -- Diseases -- Nervous System (incl. Brain); MEDICAL -- Neurology; Nervous system -- Diseases; Neurology; Neurologie; Lehrbuch; Electronic books; Electronic books; Electronic resource; Textbooks; Lehrbuch